2003
DOI: 10.2165/00023210-200317050-00002
|View full text |Cite
|
Sign up to set email alerts
|

Fatalities Associated with Therapeutic Use and Overdose of Atypical Antipsychotics

Abstract: Since 1989, several novel antipsychotic drugs have become available for use including clozapine, risperidone, olanzapine, quetiapine and ziprasidone. These agents represent a substantial improvement in the treatment of schizophrenia and related disorders and are considered to have a favourable adverse effect profile relative to traditional antipsychotics. Nonetheless, in rare cases, people have died as a result of taking atypical antipsychotic drugs at therapeutic and supratherapeutic doses. Toxic doses of aty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(50 citation statements)
references
References 89 publications
1
47
0
2
Order By: Relevance
“…Quetiapine was determined at concentrations higher than 600 ng/mL in 13 cases, at toxic levels (>1800 ng/mL) in 8 cases and at lethal level in one case (14112 ng/mL), whereas in 29 cases, its concentration was within the therapeutic range and in 8 cases at sub-therapeutic levels. These results reveal that quetiapine shows a highly variable range of toxicity and support previous published studies suggested that deaths can be occurred even with therapeutic doses [14,18,44,45]. Several factors may contribute to this variability, such as increased susceptibility of the individuals and co-ingestion of other drugs [18].…”
Section: Discussionsupporting
confidence: 88%
“…Quetiapine was determined at concentrations higher than 600 ng/mL in 13 cases, at toxic levels (>1800 ng/mL) in 8 cases and at lethal level in one case (14112 ng/mL), whereas in 29 cases, its concentration was within the therapeutic range and in 8 cases at sub-therapeutic levels. These results reveal that quetiapine shows a highly variable range of toxicity and support previous published studies suggested that deaths can be occurred even with therapeutic doses [14,18,44,45]. Several factors may contribute to this variability, such as increased susceptibility of the individuals and co-ingestion of other drugs [18].…”
Section: Discussionsupporting
confidence: 88%
“…Bizim olgumuzdaki karbamazepin dozu 35 mg/kg idi, nörolojik ve kardiak hiçbir semptom görülmedi. Antipisikotik ve antidepresan ilaçların ARDS'yi tetikleyebildiği bilinse de bununla ilgili vaka sayısı çok fazla değildir [9] . Bu araştırmalarda ARDS'ye neden olan patofizyolojik mekanizmayı açılayabilecek net bir neden olmasa da nöroleptik malign sendromun bir komponenti, nörojenik pulmoner ödem [10] akciğer dahil birçok dokuda nötrofillerin aktivasyonunu içeren bir alerjik reaksiyon [11] ve dozla ilişkili etki olduğu öne sürülmüştür.…”
Section: Discussionunclassified
“…2,3 They may also lower the seizure threshold. 4 Furthermore, both cocaine 5,6 and ziprasidone 7,8 prolong the QT interval, which may cause lethal dysrhythmias if combined. We therefore disagree with the authors' assertion that safety is implied in the setting of cocaine toxicity because the use of antipsychotics demonstrates a lack of ''significant adverse events with widespread use.''…”
Section: Use Of Antipsychotics To Treat Cocaine Toxicity?mentioning
confidence: 99%